Principios del mapuche mongen para la resignificación de la economía en tiempos de crisis del capitalismo neoliberal, desde el sur de Chile - Patricia Viera-Bravo (Revista Iberoamericana de Estudios de Desarrollo)
In the context of the current systemic crisis, neoliberal capitalism is widely questioned for its unsustainability, but there is a lack of proposals from other epistemological and ontological frameworks that allow the construction of real alternatives of economy and existence. From a critical perspective, based on a field work in the Araucanía region of southern Chile, between 2010 and 2020, in this article it is analyzed the resignification of the economy based on the systematization of the economic and life principles of the Mapuche people, based on kelluwün, or reciprocity, and the equilibrium between subject, community and biodiverse environment, with their material and immaterial dimensions necessary for the production and reproduction of life. In the reconstitution of the lof as an ancestral socio-territorial basic unit, the original conception of economy can be repositioned, centered on the oikos, the foundation of proposals for economic and political autonomy.